Anti-leukemic effects of zerumbone nanoparticle on human jurkat T lymphoblastoid cell lines in vitro and murine leukemic WEHI-3B model in vivo - Muhammad, Heshu Sulaiman Rahman (2014)
Zerumbone (ZER) is a crystalline, monocyclic, sesquiterpene, phytochemical, natural dietary substance was isolated firstly from essential volatile oil of rhizomes of the edible wild ginger, Zingiber zerumbet (L.) Smith. Recent studies showed that ZER has antiproliferative properties on several cancers. ZER has poor aqueous solubility that has inhibited cancers development as a therapeutic compound. In this study, it is postulated that ZER incorporation into nanostructured lipid carriers (NLC) will improve solubility and delivery of the compound while not comprise its therapeutic effects. Thus, the objective of the current study is to improve the therapeutic potential of ZER by incorporation into NLC and to determine the effect of ZERloaded NLC (ZER-NLC) on a human T-lymphoblastic leukemia (Jurkat) cell line and on WEHI-3B (myelomonocytic leukaemia) cell-induced murine leukemia. The ZER-NLC produced using the high pressure homogenization (HPH) technique contained 5% lipid. The ZER-NLC was characterised by zetasizer, reverse phase high performance liquid chromatography (RP-HPLC), transmission electron microscopy (TEM), wide angle X-ray diffraction (WAXR), differential scanning colorimeter (DSC) and Franz Diffusion Cell (FDC) system analyses and shown to be physically stable, particle size (PS) of 52.68 ± 0.1 nm, zeta potential (ZP) of ˗ 25.03 ± 1.24 mV and polydipersity index (PDI) of 0.29 ± 0.0041 μm. These are all characteristics of an excellent drug-carrier and delivery system. Jurkat cells were used to determine the anticancer properties of ZER-NLC. MTT assay, fluorescent microscopy, scanning and transmission electron microscopy, flow cytometric analysis after annexinV-FITC staining, cell cycle and TUNEL assay, and caspase -3, -8 and -9 assays were also employed in the study. The study showed that ZER-NLC significantly (P<0.05) suppress proliferation of Jurkat cells in vitro in a time-dependent manner with an IC50 of 12.5 ± 0.1, 9.09 ± 0.14 and 5.64 ± 0.38 μg/mL at 24, 48 and 72 h, respectively. The antiproliferative effect of ZER-NLC on Jurkat cells was attributed to induction of apoptosis via the mitochondrial (intrinsic) pathway. BALB/c mice were induced to develop leukemia with a single intraperitoneal injection of WEHI-3B cells (1 × 106 cells/animal). The in vivo study showed that oral ZER-NLC at doses of 60 mg/kg inhibited the proliferation of leukemic cells in leukemic BALB/c mice as evidenced by the decrease in leukemic cell population in the spleen. Based on histological, electron microscopic, immunochemical evaluations and TUNEL assay, the effect of ZER-NLC in the inhibition of leukemia was via apoptosis. Using Western blot and qRT-PCR, the spleen cells of ZER-NLC-treated leukemic mice also showed increased expression of Bax, Cyt-c, and PARP proteins while the expression of Bcl-2 protein decreased. At the same time, PARP protein cleaved from 116 kDa to 85 kDa. These findings also suggested that the in vivo effect of ZER-NLC on murine leukemia is apoptosis via the mitochondrial pathway. To determine potential toxicity of ZER-NLC, human peripheral blood mononuclear cells (PBMC) were treated in vitro with serial concentrations ZER-NLC up to 100 mg/mL and normal BALB/c mice treated orally with ZER-NLC at doses up to 200 mg/kg. The treatment did not produce any sign of toxicity in either normal human peripheral mononuclear cells or mice at any of the doses used, indicating that ZERNLC is safe for parenteral use. In conclusion, the study shows that loading of ZER into NLC did not reduce the therapeutic potential of compound and the in vitro effects of ZER-NLC on leukemic cells and in vivo effect on induced murine leukemia is apoptosis via the mitochondrial pathway. The ZER-NLC thus has excellent potential to be developed into a drug-carrier and delivery system for the treatment of cancers.